Comparative cost analysis of pepper farming income under certification and non-certification seeds implementation (Case in Towuti District, East Luwu Regency, South Sulawesi Province, Indonesia). Issue 1 (October 2020) - Busthanul, N; Salman, D; Syafiuddin, M; Lumoindong, Y; Amir, A; Saadah, S; Ali, Darwis; Askinner
Abstract: Certification is an activity to foster farmers about good and correct cultivation in accordance with agreed standards to improve quality and ask farmers to care for the environment, which then increases social and economic resilience so that our cultivation can be maintained. This study aims to (1) know the ongoing pepper certification process; (2) comparing income between certified pepper farming and non-certified pepper farming; and (3) understand the factors that influence income differences between pepper farming certified and non-certified pepper farming in Matompi Village, Towuti District, East Luwu Regency. Data analysis techniques used are descriptive analysis, farm productivity analysis, farming income, and R/C ratio. Analysis of farmland productivity is divided into two, namely seeds productivity and seed productivity. Seeds productivity results show that non-certified farmers are higher than certified farmers, while seed productivity results are only carried out by certified farmers. The results of the study showed, although the productivity of pepper seeds (fruit) in certified pepper farms is lower, however, is more profitable due to the high sales value of its pepper seeds (cuttings).